Training to Analyze Learning Result Test Items for High School Teachers - Hari Sugiharto Setyaedhi; Lamijan; Bakhrudin All Habsy (Universitas Pendidikan Ganesha, 2024)
Not all of the learning outcomes test items that have been developed by high school teachers have been analyzed, so they cannot be said to be quality learning outcomes tests. The problem is that most high school teachers do not understand how to analyze learning outcomes test items. The aim of this training is to increase knowledge for high school teachers about analyzing quality questions. The research subjects were 25 high school teachers, consisting of subject teacher representatives. The research method is quantitative with a one-group pretest-posttest design. Data collection techniques use experiments, observation, and pre- and post-test scores. The data analysis used in this research is a paired t-test (paired sample t-test). Process this research data using SPSS. The results of the research are in accordance with the achievement target, namely increasing the teacher's ability to analyze question items. This is proven by a significant increase in posttest scores compared to the pretest, with results in sig. (2 tailed) = 0.001 < 0.05. As proof that teachers have participated in training, they are given certificates. The implication of this service activity is to increase the competence of high school teachers in analyzing learning outcomes test items.